UNDERSTANDING OUR PAST IN THE SCHOOL EXPERIENCE (II) - Castillo Serrano, Deyanira (Universidad de Costa Rica, 2011)
This second and last part of the article UNDERSTANDING OUR PAST IN THE SCHOOL EXPERIENCE describes in detail the curriculum and the general routine of instruction that the English Schools (as they were known in Costa Rica) practiced. The purpose of the study was to develop an historical portrayal of schools for Afro- Caribbean people in Costa Rica during the first half of the 1900s. The focus of the articles is based on an oral history investigation that evolves around four key questions: 1) what were the schools of the Afro-Caribbean people in Costa Rica like during the 1934-48s? 2) How were they started? 3) What curriculum was taught in those schools? How was it taught? The selected site for the study was Limon, Costa Rica. This city has been the place of arrival and dwelling of most of the country’s Afro-Caribbean people since 1872. The qualitative methods used provided evidence to answer the research questions. The interviews followed the guidelines of oral history inquiry (i.e., with consent and agreement forms presigned). The data collected revealed that the English Schools were supported by different church denominations, the railroad company, the United Fruit Company, and the Universal Negro Improvement Association. The curriculum and instruction used permitted to find similarities between the English Schools and the primary schools designed for the British colonies, particularly Jamaica.